The impact of globalization on family–structure: a sociological study (In reference to the 300 bengali families situating in Udham Singh nagar district of Uttarakhand). - Kumar, Anchalesh (Journal of Experimental Sciences, 2012)
In the present research paper, we shall discuss a study which has been carried out on the Bengali community situating in the lowlands (Tarai) of the Udham Singh Nagar district of Uttarakhand and the effect of Modernization and Globalization on their family structure on this community. Its historicity lies in the fact that the Bengali community living in the lowlands of Udham Singh Nagar has all come from East Pakistan (Now Bangladesh) and mainly from its three districts viz. Khulna, Faridpur and Jasaur.